PI-3 Committees of the 1st Colombian Congress of Natural Products (2025) - Isaza Martienz, José Hipólito (Revista Productos Naturales, 2025)
The document outlines the committees for the I Colombian Congress on Natural Products scheduled for 2025, detailing the members of the Organizing Committee, Scientific Committee, and Editorial Committee, including their affiliations and roles.